inflammation increases the resting energy expenditure in hemodialysis patients - Viviane O Leal; Milena B Stockler-Pinto; Julie C Lobo; Najla E Farage; Denis Fouque; Denise Mafra (The Korean Society of Nephrology, 2012)
Resting energy expenditure (REE) is the predominant component of total daily energy expenditure (TEE). Metabolic disorders and comorbities, such as inflammation and diabetes, can affect the REE in hemodialysis (HD) patients. The objective of this study was to evaluate the relationship between inflammation and REE estimated by TEE in HD patients. Twenty-five HD patients (54.5±11.7 years, 15 men, BMI, 24.4±4.7 kg/m2, urea clearance (Kt/Vsp) of 1.43±0.26 and 58.2±42.7 months on HD) were studied. TEE was measured during two days (one dialysis and one fx1 nondialysis day) by SWA (SenseWear Pro2 Armband, BodyMedia Inc, Pittsburgh, PA, USA). This monitor provides directly the TEE and the physical active energy expenditure (PAEE); the REE measurement was obtained by the subtraction of PAEE and thermic effect of food (approximately 10% of TEE) from TEE. C-reactive protein (CRP) was measured by immunoturbidimetric method. The REE was 1677.7±273.5 kcal/d for men and 1267.0±221.6 kcal/d for women (p〈0.0001). The CRP levels values were 0.27 ± 0.26 mg/dL and nine patients (36%) had CRP 〉0.3 mg/dL, compatible with chronic inflammation. A trend for high REE was observed in patients with inflammation (1865±216 kcal/d for men with CRP≥0.3 mg/dL and 1584±257kcal/d with CRP〈0.3 mg/dL (p= 0.05); 1361.4±181.5 kcal/d for women with CRP≥0.3 mg/dL and 1204.1±238.2kcal/d with CRP〈0.3 mg/dL (p = 0.27). CRP was positively correlated with REE (r=0.41; p=0.04). In conclusion, chronic mild inflammation can increase the REE in HD patients.